(3GdGSJQGJjLjGJ GdJShjbjI dNOeGJ GdecJHGJ hGdeYdheGJ HGdecJHGJ GdeQcRjI aj GdLGeYGJ GdeUQjI (B: s (3OQGSI JbjjejI (B/s - (3,QVhi eMeO eMeO MejOIs; (3TQja cGed TGgjfs; (3SMQ MSfjf QHjYs (2025)
(3JgOa GdOQGSI Edi Jbqjje GdGSJQGJjLjGJ GdJShjbqjI GdeJHYI aj GdecJHGJ GdeQcRjI HGdLGeYGJ GdeUQjI, hJSdjW GdVhA Ydi OhQgG aj JMSjf eSJhi NOeGJ GdecJHGJ hRjGOI QVG GdeSJajOjf(B. (3GSJNOeJ GdOQGSI efgkLG hUakjG JMdjdkjG dLeY GdHjGfGJ ef YOO ef GdecJHGJ GdeQcRjI aj GdLGeYGJ GdeUQjI, ef NdGd bGFeI eQGLYI eMceI hGdebGHdGJ eY eOQGA GdecJHGJ GdeQcRjI hGdeSDhdjf(B.(3JfGhdJ GdOQGSI YOI eMGhQ QFjSI, efgG(B:-(3JMdjd hGbY GdGSJQGJjLjGJ GdJShjbjI GdeJHYI, heOi aYGdjJgG aj LPH GdeSJajOjf(B.-(3MOjO GdJMOjGJ GdJj JhGLg GdecJHGJ aj JWHjb gPg GdGSJQGJjLjGJ(B.-(3GSJcTGa JCKjQ JWHjb GdGSJQGJjLjGJ GdJShjbjI Ydi RjGOI GdEbHGd Ydi NOeGJ GdecJHGJ hJMbjb GdGSJOGeI(B.(3CXgQJ GdfJGFL Cnqf gfGc JaGhkJG aj GSJNOGe GdecJHGJ GdeQcRjI GdLGeYjI ddGSJQGJjLjGJ GdJShjbjI, MjK jYJeO HYVgG Ydi CSGdjH JbdjOjI, HjfeG JHfJ ecJHGJ CNQi eKGd ecJHI LGeYI eUQ ddYdhe hGdJcfhdhLjG JbfjGJ MOjKI eKd GdJShjb GdEdcJQhfj hefUGJ GdJhGUd GdGLJeGYj, ceG cTaJ GdOQGSI Edi VQhQI JWhjQ GSJQGJjLjGJ JShjbjI eHJcQI hTGedI JhGcH GdJZjQGJ GdJcJhdhLjI GdeSJeQI, hGdJQcjR Ydi JhXja GdJcJhdhLjG GdMOjKI hRjGOI GdhYj HCgejI GdJShjb Hjf GdYGedjf aj GdecJHGJ(B. (3hbOeJ GdOQGSI eLehYI ef GdJhUjGJ dJMSjf GdELQGAGJ GdJShjbjI hRjGOI JCKjQg aj QaY eSJhi NOeGJ GdecJHGJ GdLGeYjI(B.s
The study aims to evaluate the marketing strategies followed in central libraries in Egyptian universities, and to highlight their role in improving the level of library services and increasing beneficiary satisfaction. The study used a descriptive analytical approach to collect data from a number of central libraries in Egyptian universities through a rigorous checklist and interviews with central library directors and officials. The study addressed several main elements, including: -Analyzing the reality of the marketing strategies followed, and their effectiveness in attracting beneficiaries. -Identifying the challenges facing libraries in implementing these strategies. -Exploring the impact of implementing marketing strategies on increasing demand for library services and achieving sustainability. The results showed that there is a disparity in the use of university central libraries of marketing strategies, as some of them rely on traditional methods, while other libraries, such as the Misr University Library for Science and Technology, have adopted modern technologies such as electronic marketing and social media platforms. The study also revealed the need to develop innovative and comprehensive marketing strategies that keep pace with ongoing technological changes, and to focus on employing modern technology and increasing awareness of the importance of marketing among library workers. The study presented a set of recommendations to improve marketing procedures and increase its impact in raising the level of university library services.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2025. s
(3HHdjhLQGajG(B: (3UaMGJ (B175-186.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdecJHGJ GdLGeYjIs; (3GdGSJQGJjLjGJ GdJShjbjIs -- (3GdecJHGJ GdLGeYjIs -- (3GdeRjL GdJShjbjs